Involvement of the General Public in the Management of Water Pollution in Johor Bahru Malaysia - Sanda, B. Y.; Bah, A. U.; Ibrahim, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Water is undoubtedly the most delicate component of the ecosystem, but it is essential for human and industrial advancement. As the population grows, so does the demand for water supplies and drinkable water. Water covers roughly 71percent of the total earth’s surface and highly vital natural resource for humans. However, only 2.5 percent of the world's water is pure and thus drinkable. It is everyone's fundamental human right to have access to clean water. The purpose of this study is: to identify the current level of public involvement in water pollution management and to assess people's desire to participate towards reducing water pollution. The study's methodology is a quantitative approach for achieving the research objectives. A total of sixty-three (63) responses were reordered from the distribution of the questionnaires. The data collected were analysed using Microsoft Excel (2019) and simple percentage distribution tables and charts. The findings revealed that most of the participants have sewerage connections in their residences and that the water quality of their rivers is acceptable for majority of the participants. The study also indicated that water pollution is a grave concern for environmental and social health. In addition, it was observed that community involvement in water pollution decision-making processes was currently low on average, implying that authorities still have room to improve concerning water pollutant information delivery. Majority of respondents agreed that investing more money in water and waste management, and educating the public, are strategies to enhance water quality. Eventually, the findings revealed that the general public is enthusiastic about taking part in the fight against water pollution and are ready to participate in water pollution management in their community. The study recommends building a solid foundation to allow greater public involvement in decision-making and to enacting strict water pollution control policy.